Pengawasan Fasilitas Dengan Metode MBO (Management By Objectives) Di Area Apron Pada PT. Angkasa Pura I Bandar Udara Internasional Yogyakarta. - Neng Winda; Yunus Purnama (Pusat Riset dan Inovasi Nasional, 2023)
The supervision carried out by AMC is for all movements on the apron during take off and landing. The purpose of this study was to determine the performance evaluation of the apron movement control (AMC) unit in monitoring facilities in the apron area, constraints on facilities in the apron area, and solutions to constraints on facilities in the apron area at PT. Angkasa Pura I Yogyakarta International Airport. This research was conducted for 1 month, namely in March 2023 which was conducted at Yogyakarta International Airport, this research is a qualitative research. Primary data obtained directly by observation and interviews. Secondary data obtained indirectly through documentation, literature and company data. Data collection techniques using observation methods, semi-structured interviews, and documentation. The results of the research were tested for the validity of the data using source, technique, and time triangulation. The result of the study is the evaluation of the performance of the AMC unit in monitoring facilities in the apron area using the MBO (Management by Objectives) method based on planning, monitoring and review. There are several problems with facilities in the apron area such as aviobridge 4C, 8A and 8C are damaged, aviobridge 4C slowdown is too slow, GSE is parked in No Parking Area (NPA), there is no Equipment Parking Area (EPA) marking, GSE is parked below fixbridge, CCTV error/connection to server fails, and CCTV is blurry if the weather is rainy. Some of the solutions for the problem facilities in the apron area are waiting for spare parts, coordinating with the mechanical unit, reprimanding and ordering groundhandling to move the GSE, reporting EPA markings to be added, and reporting to the ICT unit.